Insurer Liability for Medically Related Motor Vehicle Accident Costs in Alberta - Jacobs, Philip; Lier, Douglas; Schopflocher, Donald (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2004)
In Alberta, automobile insurers are liable for medical costs of casualties who are not responsible for the accident. There is a levy ($43 million in 1999) but there is also a considerable degree of uncertainty about the amount that should be transferred for medical costs. We conducted an analysis of these costs that included the following data: motor vehicle accident claims for most insurance companies in Alberta in 1999 (which were linked to provincial health insurance registrations); all hospitalizations and emergency room visits in the province that were related to motor vehicle accidents; records (physician, inpatient hospital, outpatient hospital, ambulance, insured drugs) for subsequent one year post accident utilization; and unit administrative costs for health services, set by the province. A second analysis, using 1997 - 2000 data and only hospital inpatient and emergency admissions, was conducted for 3 year utilization experience, and projected beyond. Liability reduction factors were obtained from provincial transportation statistics. Our results indicated that total costs (using administrative prices) amounted to $119 million in 1999 and estimated liability was $82 million. Several areas of uncertainty remained; these included the actual costs beyond three years post - accident, the relationship of administrative prices to actual resource costs; and the roles played in liability by other groups (Workers Compensation and non-insured drivers). This study forms a basis for setting the insurance levy which is more objective than methods used before.